|Vol. 6| No. 1|Year 2019 - Editorial Team (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2019)
Edukasi: Jurnal Pendidikan dan Pengajaran provides a vital forum for exchanging ideas in order to enrich the theories and practices of English education in Indonesia and across the globe. The journal focuses, but not limited to, on the following topics: English language teaching, language teaching and learning, language teaching methodologies, pedagogical techniques, teaching and curricular practices, curriculum development and teaching methods, program, syllabus, and materials design, second and foreign language teaching and learning, language education, teacher education and professional development, teacher training, cross-cultural studies, bilingual and multilingual education, translation, language teaching for specific purposes, new technologies in language teaching, and testing and evaluation. It provides an academic platform for teachers, lecturers, and researchers to contribute innovative work in the field.